Pendampingan Program Pemberian Makanan Tambahan (PMT) Lokal Sebagai Perubahan Status Gizi Balita Desa Jangur Kabupaten Probolinggo - Adhiva Calista Ajiputri; Winda Elmira Amanda; Lala Sevina Putri; Lylu Tirta Damayanti; Katerina Bataha (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Providing Local Supplementary Food (PMT) is one of the strategies for handling toddler nutrition problems. Through the assistance of the Local PMT program in Jangur Village, it aims to reduce the problem of malnutrition and the risk of stunting in toddlers. Community service activities carried out by KKNT 55 students at the East Java "Veteran" National Development University were carried out for 14 days, starting from 20 May to 02 June 2023 with the target of 25 toddlers who experienced weight loss in Jangur Village. The method of implementing community service is Local PMT assistance which is carried out through three stages, namely planning, implementing and monitoring. The aim is to increase public awareness about child development and stunting prevention, especially in Jangur Village, Sumberasih District, Probolinggo Regency. The results of the Local PMT assistance activities show the effectiveness of the PMT program on changes in the nutritional status of toddlers in Jangur Village.